Racial Disparities in Access to Dental Care: A Secondary Analysis of the California Health Interview Survey 2023 - Khadim Hussain , Hamid; Vosooghinezhad , Behzad; Tavakol, Omid; Khoshnevisan, Mehrnoosh; Gholami , Mahnaz; Khayamzadeh, Mina; Karimzadeh, Moslem (Galen Medical Journal, 2024)
Background: Racial disparities in dental health care access have been a persistent issue in the United States. This study aims to investigate the association between racial disparities and access to dental care. Materials and Methods: This study conducted a secondary data analysis of the CHIS 2023 Adult Survey, which included a sample of 21671 individuals. The survey collected information on demographic characteristics, health behaviors, and dental health outcomes, including access to dental care. Ordinal regression analysis was performed to examine the association between racial disparities and dental service outcomes, controlling for demographic and socioeconomic factors. Results: The study found significant differences in demographic characteristics among racial groups. The 2023 CHIS analyzed 21,671 individuals across various racial groups, revealing significant variations in age distribution, with White individuals being the oldest and "Other single race" the youngest. Whites also had the highest median income and dental insurance coverage. An ordered logistic regression adjusted for age, gender, educational level, income last month, current smoking status, and dental insurance showed that being White was associated with a significantly higher number of dental visits (coefficient = 0.14, p-value = 0.005), while other racial groups did not show significant associations. Conclusion: This study suggests that racial disparities exist in dental service outcomes in California, with certain racial and ethnic groups being less likely to access dental care. The findings show the need to address these disparities and improve access to dental care for marginalized populations.